The Experience with Transcatheter Ablation of Supraventricular Tachycardia in Puertorican Adults - García-Burgos, José O.; Jiménez, Raúl A.; Mercado, Caleb; Ortiz, Pedro; Rodríguez, Angel; Abreu, Miguel; Delgado-Osorio, Héctor (Puerto Rico Health Sciences Journal, 2010)
see manuscript